Pengaruh Perhatian Orangtua dan Minat Belajar Matematika Terhadap Prestasi Belajar Matematika Siswa - Santy Handayani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2016)
The study objective was to determine of the parents attention and interest in learning to learn mathematics achievement. The method used in this study is a survey method. Sample size of 100 students obtained by random from two schools. Data collection doing by direct observation, documents student achievement of each grade math teacher and school and questionnaire. Analysis of the data with descriptive statistical method, multiple correlation coefficient, determination coefficient and regression analysis. Results of the hypothesis tests, namely (1) there is no influence of the parents attention and interest in learning mathematics to the students learning achievement (2) the role of parental not significantly affects mathematics achievement (3) student interest significantly affect mathematics achievement. Keywords: Parents attention, interest in learning, mathematics achievement.